PROFIL RESPONS SISWA DALAM MEMECAHKAN MASALAH ALJABAR BERDASARKAN TAKSONOMI SOLO DITINJAU DARI MINAT BELAJAR MATEMATIKA - Laisouw, Ruslan (Jurnal Pembelajaran Matematika, 2013)
Abstract: The objective of this research is to investigate the profile of response in solving SOLO taxonomy-based algebra problems of the students in Grade VIII with the high, medium, and low Mathematics learning interests. Structure of Observed Learning Outcome (SOLO) taxonomy is a framework to classify the students’ response comprising 4 levels. The subjects of the research consisted of six students in Grade VIII of MTA junior Secondary School of Gemolong, Sragen in academic year 2011/2012.The instrumen used were test instrument, and the interview guideline.the data analysis so as to find out the response in solving SOLO taxonomy-based algebra problems.The results of the research are as follows. The response levels in solving SOLO taxonomy-based algebra problems of two subjects with the high Mathematics learning interest belong to extended abstract level (level 4).The response levels of two subjects with the medium Mathematics learning interest in solving SOLO taxonomy-based algebra problems are different from one to the other; one of them has the relational level (level 3) while the other has the multi-structural level (level 2). For this case, the students with the same Mathematics learning interest category (medium level) have the have different response.The response levels of two subjects with the low Mathematics learning interest in solving SOLO taxonomy-based algebra problems are also different from one to the other; one of them has the multi-structural level (level 2) while the other has uni-structural level (level 1). For this case, the students with the same Mathematics learning interest category (low level) have the different response.Key words: Students’ response level, algebra problems, SOLO taxonomy, and Mathematics learning interest